2019
DOI: 10.1093/jat/bkz078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Toxic Metals in Electronic Cigarette Aerosols Using a Novel Trap Design

Abstract: Since 2006 the domestic popularity and sales of electronic cigarettes (i.e., electronic nicotine delivery systems or ENDS) have grown rapidly. Although the constituents of the aerosol produced by ENDS have been previously investigated, differences in puff regimens and aerosol trapping schema in published literature often complicate result comparisons and data interpretation. As the ENDS product designs continue to evolve, there is a critical need to develop and validate robust methodologies for laboratory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 21 publications
4
44
1
Order By: Relevance
“…Measurable cadmium has been reported in ENDS liquids [7] and in manuscripts on metals in aerosol [12,13]. However, there are no ENDS devices for which cadmium has been reported as a device component, nor did our SEM-EDS, liquid results, or previously reported aerosol results [3] determined detectable cadmium.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Measurable cadmium has been reported in ENDS liquids [7] and in manuscripts on metals in aerosol [12,13]. However, there are no ENDS devices for which cadmium has been reported as a device component, nor did our SEM-EDS, liquid results, or previously reported aerosol results [3] determined detectable cadmium.…”
Section: Resultsmentioning
confidence: 63%
“…The studies showed that metals significantly increased after contact with a device and concluded that the devices transfer metals to the liquid. The My Vapor Store liquid was added to a Joyetech eGo tank system in our previous study, and the aerosol showed detectable nickel, copper, zinc, tin, and the highest of the analyzed lead [3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations